Immunomodulatory peptides: new therapeutic horizons for emerging and re-emerging infectious diseases - Chatterjee, Debolina; Sivashanmugam, Karthikeyan (Frontiers in Microbiology, 2024)
The emergence and re-emergence of multi-drug-resistant (MDR) infectious diseases have once again posed a significant global health challenge, largely attributed to the development of bacterial resistance to conventional anti-microbial treatments. To mitigate the risk of drug resistance globally, both antibiotics and immunotherapy are essential. Antimicrobial peptides (AMPs), also referred to as host defense peptides (HDPs), present a promising therapeutic alternative for treating drug-resistant infections due to their various mechanisms of action, which encompass antimicrobial and immunomodulatory effects. Many eukaryotic organisms produce HDPs as a defense mechanism, for example Purothionin from Triticum aestivum plant, Defensins, Cathelicidins, and Histatins from humans and many such peptides are currently the focus of research because of their antibacterial, antiviral and anti-fungicidal properties. This article offers a comprehensive review of the immunomodulatory activities of HDPs derived from eukaryotic organisms including humans, plants, birds, amphibians, reptiles, and marine species along with their mechanisms of action and therapeutic benefits.